Thematic approach and its effectiveness in improving learning outcomes, motivation, and critical thinking in natural and social sciences - Tulus Tulus; Aunurrahman Aunurrahman; Halida Halida; Hesti Dahlan; Ndaru Wigati; Hadi Mulya (CV. FOUNDAE, 2024)
Background: Thematic learning is an effective strategy to address the demands of 21st-century education by integrating critical thinking, collaboration, and creativity through contextual learning environments.Aim: This study aims to evaluate the effectiveness of the thematic approach in improving students' learning outcomes, motivation, and critical thinking skills in Natural and Social Sciences (IPAS) subjects at SMKN 1 Sukadana.Method: The research employed a quasi-experimental design with a pretest-posttest control group. A total of 70 grade XI students were selected as the sample through purposive sampling, divided into experimental and control groups (35 students each). Data were collected using learning outcome tests, motivation questionnaires, and observation sheets. Descriptive and inferential statistical analyses, including t-tests, were conducted after normality and homogeneity tests.Results: The thematic approach significantly enhanced learning outcomes, motivation, and critical thinking skills. The experimental group achieved a 100 percent success rate, compared to 48.57 percent in the control group. Variance in individual responses highlighted differing adaptations to this method.Conclusion: The thematic approach is effective in improving student engagement, motivation, and interdisciplinary learning outcomes, particularly in vocational education. These findings support its implementation as a cross-disciplinary teaching method and provide insights for educational policy development.